Pengaruh Dampak Variasi Piston Diameter 58 ML Dan 52 ML Terhadap Kinerja Motor Matic 4 Tak 110 - Alvin Nurfaiz; Dida Ardito Yudhistira; Dwi Istiyarno; Trisma Jaya Saputra (Pusat Riset dan Inovasi Nasional, 2023)
This research was conducted to determine the effect or impact of variations in the size of a standard piston diameter (52 ML) with a piston with a diameter of 58 ML on a Yamaha Mio motorbike using a dyno test. The results we got from the dyno test, the power or horsepower (HP) produced from a motorbike with a standard 52 ML piston size is 7.44 HP at Rpm 7000 and a torque of 8.72 Nm. Meanwhile, the modified motor with a 58 ML piston produces 11.37 HP at 7000 Rpm and 11.10 Nm of torque. And it can be concluded that motors with factory original standard pistons measuring 52 ML have much lower torque and power than modified pistons measuring 58 ML and the fuel consumption of motors with modified pistons will be more or more wasteful.